"Analyzing IFRS 18: A New Framework for Presentation and Disclosure in Financial Statements and Implementation Challenges" - djemai, mohammed salah (Journal of Research in Finance and Accounting, 2025)
This study examines IFRS 18, issued in 2024, as a conceptual shift in financial reporting and disclosure. The standard seeks to enhance comparability and increase transparency by requiring companies to present standardized operating items and disclose internally developed performance measures. The analysis shows that IFRS 18 marks a notable improvement over IAS 1, yet poses implementation challenges, especially in weak regulatory environments. The study recommends adapting practical guidance, building professional capacity, and applying the standard gradually. Findings are based on a recent literature review and comparative analysis of key professional texts